Criar, resistir, comunicar: a ambivalência política dos Novos Coletivos - Martins, Giancarlo (2015)
This thesis analyses the manner artistic collectives have been transformed during the last decade, introducing new ways of communication and political action. The main hypothesis is that the fact they do not fit in the criteria of community as proposed in the first half of the twentieth century, it does not mean they have surrendered to the control society or the power devices of the late capitalism. That means a change in the ways of communicating and acting collectively and such experiences have not been sufficiently analysed yet concerning to art theories, asking for new proposed epistemological discussion, especially in the areas of communication and culture studies (Katz and Greiner, Lipovetski, Canclini, Sennett) and political philosophy (Foucault, Virno, Negri, Agamben). The corpus of this research is composed by collective experiences acting in Curitiba and São Paulo, and has proposed a kind of sharing which recognizes the singularities and discontinuity of the subjects in the collective field. The expected result is the presentation of an emerging field of experiences which describe the need of thinking about new manners of acting and creating collectively